Optical, optoelectronic, and photoelectric properties in moiré superlattices of twist bilayer graphene. (August 2020) - Wang, J.; Bo, W.; Ding, Y.; Wang, X.; Mu, X.
Abstract: Graphene's zero-bandgap energy band structure limits its electrical applications but gives it superior optical and optoelectronic properties. In twisted bilayer graphene (TwBLG), a periodic superlattice is formed by asymmetric lattice and twisted angles. Some new electron states appear between layers. As the twisted angles change, the energy difference between the Van Hove singularity also obviously changes. At this point, the optical and photoelectrical properties of TwBLG improve considerably. The optical absorption is significantly selectively enhanced, providing better photoelectric performance, faster photochemical reaction rates, and novel nanoscale photonic crystal structures. In this article, we review the properties and potential applications of TwBLG in optics and optoelectronics. Graphical abstract: Image 1 Highlights: Relationship between twisted bilayer graphene (TwBLG), twisted angle, and optical properties. The TwBLG chiral spectrum is achieved by the twisted angle. TwBLG photoelectricity, photo-thermoelectric property change caused by different angles.